Family and marriage counseling and HIV/AIDS pandemic in Nigeria - Okwun, K.C.; Siraj, Saedah (2010)
The success of retrovirus therapy has prompted many of the infected HIV/AIDS serodiscondents couples to now live healthier lives and pursuing a wider range of activities. Many HIV/AIDS infected women today can participate in having their babies, with a significant chance of living to see their children grow into adulthood without infection. Based on the foregoing, the authors carried out qualitative interview research to determine the child bearing desires of serogative couple. Study findings show that two thirds of the interviewed women have high desires to have babies despite having full knowledge of their health condition. The authors conclude that collaborative partnership between family planning and HIV/AIDS services and HIV counseling as part of the integrated system will provide early intervention services to provide relief of anxiety about reproduction in an HIV infected woman to reduce HIV transmission and marriage breakup.